2011
DOI: 10.1007/s00259-011-1751-y
|View full text |Cite
|
Sign up to set email alerts
|

99mTc-MAA/90Y-Bremsstrahlung SPECT/CT after simultaneous Tc-MAA/90Y-microsphere injection for immediate treatment monitoring and further therapy planning for radioembolization

Abstract: Combining RE and Re-MAA is feasible in appropriately selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…At present, biodistribution of 90 Y after treatment is generally assessed through Bremsstrahlung SPECT [12] or 99m Tc SPECT [13] images if during therapy MAA particles are administered after microsphere injection. Nevertheless, both techniques present important drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…At present, biodistribution of 90 Y after treatment is generally assessed through Bremsstrahlung SPECT [12] or 99m Tc SPECT [13] images if during therapy MAA particles are administered after microsphere injection. Nevertheless, both techniques present important drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…The radioembolized left renal mass and bilateral lungs demonstrated 90 Y radioactivity on posttherapy bremsstrahlung imaging and the bilateral lung radioactivity was presumed arteriovenous shunting of microspheres through the tumor and then trapped in the lungs. Subsequently, others have described posttherapy planar bremsstrahlung imaging for patients following direct injection of 90 Y (e.g., radiosynovectomy) [5, 6], intravenous administration of 90 Y-labeled RIT [26], and intra-arterial administration of 90 Y-labeled microspheres [2731]. In addition, one study demonstrated the capability for planar bremsstrahlung imaging to detect focal 90 Y radioactivity using a phantom model simulating soft tissue extravasation of an intravenous 90 Y dose [32].…”
Section: Bremsstrahlung Radiationmentioning
confidence: 99%
“…Subsequently several other clinical studies have described posttherapy SPECT and/or SPECT/CT bremsstrahlung imaging for patients following direct injection of 90 Y [47], intravenous administration of 90 Y-labeled RIT [2, 26] and PRRT [47], and intra-arterial administration of 90 Y-labeled microspheres (resin [14, 2931, 44, 4859], glass [54, 6063], or not specified [64]). Table 1 lists the previously reported image acquisition settings used for clinical 90 Y bremsstrahlung planar and SPECT imaging.…”
Section: Bremsstrahlung Radiationmentioning
confidence: 99%
“…A medium-energy collimator, instead of a low-energy all-purpose collimator, will optimize imaging of the 140-keV photons of 99m Tc-MAA by eliminating most of the higher-energy photons of the bremsstrahlung radiation. A low-energy high-resolution collimator can also be used (31). Narrowing the energy window to 10% will further reduce the amount of scattered bremsstrahlung photons reaching the detectors.…”
Section: Optimization Of the Imaging Protocol In Concurrent Administrmentioning
confidence: 99%